Bijective point maps, point-stationarity and characterization of Palm measures - Heveling, Matthias (KIT Scientific Publishing, 2006)
In the theory of stationary spatial point processes, Palm distributions are used to describe the point process seen from one of its points. Such an intrinsic frame of reference is not only interesting for theoretical considerations, but also useful in related fields such as queuing theory and stochastic geometry.